Motor vehicle technology - Arora (Engineering series, 2010)
Motor Vehicle Technology is a part of the Engineering Series published specifically for Technical and Engineering students and those with interest in this subject. The main objective of this book is to provide a basic knowledge in machinese technology, in a very simple, lucid and understandable language. Numerous tables, diagrams and illustrations are used to further explain the subject for easy comprehension of the reader. Each chapter is well planned and the lucid style of narration will make the students grasp the idea easily.